1993
DOI: 10.1007/bf00327842
|View full text |Cite
|
Sign up to set email alerts
|

Production of alkaline xylanase by a newly isolated alkaliphilic Bacillus sp. strain 41M-1

Abstract: Alkaliphilic Bacillus sp. strain 41M-1, isolated from soil, produced xylan-degrading enzymes extracellularly. Optimum pH for the crude xylanase preparation was about pH 9, confirming the production of novel alkaline xylanase(s) by the isolate. Xylanases were induced by xylan, but were not produced in the presence of xylose, arabinose or glucose. Xylanase productivity was influenced by culture pH, and production at pH 10.5 was higher than that at pH 8.0. Zymogram analysis of the culture supernatant showed the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
65
1
6

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 10 publications
3
65
1
6
Order By: Relevance
“…One unit of activity (U) is defined as the amount of enzyme capable of releasing reducing sugars equivalent to one mole of xylose per minute under the conditions described [21]. was also performed.…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…One unit of activity (U) is defined as the amount of enzyme capable of releasing reducing sugars equivalent to one mole of xylose per minute under the conditions described [21]. was also performed.…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…strains from soil produced multiple xylanases extracellularly. 63),64) One of the enzymes, xylanase J, was most active at pH 9.0. The optimum temperature for the activity at pH 9.0 was around 50˚C.…”
Section: )mentioning
confidence: 99%
“…On the other hand, an XBD truncated XynJ derivative (∆XBD), and a fusion protein of glutathione S transferase (GST) and the XBD (GST XBD) were prepared. 6,7) GST XBD bound tightly to insoluble xylan and ∆XBD showed far lower hydrolyzing activity toward insoluble xylan than full length XynJ. These results indicated that the XBD would bind to insoluble xylan and enhance hydrolyzing activity of the adjacent CatD.…”
mentioning
confidence: 94%
“…41M 1 from a soil sample. 4) The strain produced a xylanase that had an alkaline pH optimum. 5) The enzyme, named xylanase J (XynJ), consists of two functional domains: a glycoside hydrolase (GH) family 11 catalytic domain (CatD) and a xylan binding domain (XBD) belonging to carbohydrate binding module family 36 (http: www.…”
mentioning
confidence: 99%
See 1 more Smart Citation